COMPETITIVENESS IN THE BUILDING MATERIALS MARKET: INFLUENCING FACTORS - Samoilenko, Antonina; Lyalina, N.P.; Yudicheva, O.P. (SWorld-Ger Conference proceedings, 2025)
The article examines the factors influencing the introduction and increase of competitiveness in the building materials market. The main factors determining the level of competitiveness of products are divided into internal and external. Internal factors